Histopathological study of soft tissue tumours in a tertiary health centre in southern part of Assam - Tapadar, Khadija S.; Deka, Manoj K.; Chaubey, R. N.; Sheikh, Shah A.; Choudhury, Gargi R.; Choudhury, Madhusmita (International Journal of Research in Medical Sciences, 2021)
Background: Soft tissue tumors are defined as mesenchymal proliferations which occur in the extraskeletal non-epithelial tissues of the body, excluding the viscera, coverings of brain and lymphoreticular system. The objective of this study was to study the histopathological features of soft tissue tumors and to study the occurrence of soft tissue tumors in relation to age, sex and anatomical site. Methods: This study comprised of 89 cases studied over a period of two years. All soft tissue tumors, their gross features, microscopic findings were analysed in detail. Soft tissue tumors were divided into benign and malignant categories and further sub typing were done according to World Health Organization (WHO) classification. The distribution of soft tissue tumors according to the age, sex and site of occurrence was studied. Results: Out of 89 cases of soft tissue tumors, 76 cases were benign, 4 cases belonged to intermediate category and 9 cases were malignant. Adipocytic tumors formed the largest group constituting 39 cases. Vascular tumors were the second commonest (26 cases) followed by peripheral nerve sheath tumors (11 cases). The benign tumors were seen in younger age as compared to malignant tumors. Malignant soft tissue tumors was seen to be more common in male than female and pleomorphic sarcoma and liposarcoma was commonest (3 cases each). Conclusions: Benign tumors were more common than malignant. The most common benign tumors were lipoma followed by hemangioma and schwannoma. The most common malignant tumor was pleomorphic sarcoma. The benign tumors were seen in younger age as compared to malignant tumors.